Transcriptomic analysis of Staphylococcus xylosus in the presence of nitrate and nitrite in meat reveals its response to nitrosative stress - Vermassen, Aurore; de la Foye, Anne; Loux, Valentin; Talon, Régine; Leroy, Sabine (Frontiers in Microbiology, 2014)
Staphylococcus xylosus is one of the major starter cultures used for meat fermentation because of its crucial role in the reduction of nitrate to nitrite which contributes to colour and flavour development. Despite longstanding use of these additives, their impact on the physiology of S. xylosus has not yet been explored. We present the first in situ global gene expression profile of S. xylosus in meat supplemented with nitrate and nitrite at the levels used in the meat industry. More than 600 genes of S. xylosus were differentially expressed at 24 or 72 hours of incubation. They represent more than 20% of the total genes and let us to suppose that addition of nitrate and nitrite to meat leads to a global change in gene expression. This profile revealed that S. xylosus is subject to nitrosative stress caused by reactive nitrogen species generated from nitrate and nitrite. To overcome this stress, S. xylosus has developed several oxidative stress resistance mechanisms, such as modulation of the expression of several genes involved in iron homeostasis and in antioxidant defence. Most of which belong to the Fur and PerR regulons, respectively. S. xylosus has also counteracted this stress by developing DNA and protein repair. Furthermore, it has adapted its metabolic response—carbon and nitrogen metabolism, energy production and cell wall biogenesis—to the alterations produced by nitrosative stress.